Structural change in an open economy - Timothy Uy; Kei-Mu Yi; Jing Zhang (Federal Reserve Bank of Chicago, 2013)
We study the importance of international trade in structural change. Our framework has both productivity and trade cost shocks, and allows for non-unitary income and substitution elasticities. We calibrate our model to investigate South Korea's structural change between 1971 and 2005. We find that the shock processes, propagated through the model's two main transmission mechanisms, non-homothetic preferences and the open economy, explain virtually all of the evolution of agriculture and services labor shares, and the rising part of the hump-shape in manufacturing. Counterfactual exercises show that the role of the open economy is quantitatively important for explaining South Korea's structural change.
Keywords: F20; F40; O13; O41; 330; structural transformation; international trade; sectoral labor reallocation